Lactate released by Muller glial cells is metabolized by photoreceptors from mammalian retina - Poitry-Yamate, CL (J Neurosci, 1995)
The nature of fuel molecules trafficking between mammalian glial cells and neurons was explored using acute retinal cell preparations of solitary Muller glial cells, Muller cells still attached to photoreceptors (the “cell complex”), and solitary photoreceptors. 14C- Molecules in the cell complex, Muller cells, and respective baths were quantitated following 30 min incubation in bicarbonate-buffered Ringer's solution carrying 5 mM 14C(U)-glucose, and substrate preference by solitary photoreceptors was assessed by measuring 14CO2 production. Muller cells alone metabolized 14C-glucose predominantly to carbohydrate intermediates, while the presence of photoreceptors raised proportionately the amount of radiolabeling in amino acids. 14C-Lactate was the major carbohydrate found in the bath. However, in the presence of photoreceptors, its amount was 70% less than that for Muller cells alone. This decrease matched the expected production of 14CO2 by photoreceptor oxidative metabolism and was antagonized by the addition of unlabeled lactate. Moreover, while solitary photoreceptors consumed both exogenous 14C-lactate and 14C-glucose, lactate was a better substrate for their oxidative metabolism. In the cell complex, the metabolism of amino acids increased and illumination affected primarily glutamate and glutamine production: the specific activity of glutamate changed in parallel with that of lactate, and that of glutamine increased by eightfold in darkness. These results demonstrate transfer of lactate from Muller cells to photoreceptors and underscore a photoreceptor-dependent modulation of lactate and amino acid metabolism. We propose that net production and release of lactate by Muller cells serves to maintain their glycolysis elevated and to fuel mitochondrial oxidative metabolism and glutamate resynthesis in photoreceptors.